''Everywhere is becoming the same''? labour utilisation, regulation and the tensions inherent in transnational IT production. (1st October 2008) - ,; ,
Abstract : Does the internationalisation of economic activities reduce the differences between locations in core and peripheral regions of capitalist production? This article contributes to this discussion by emphasising an inherent contradiction of transnational production: companies must draw upon divergent regulatory scenarios and strategies of labour utilisation and articulate them in their organisational structures in order to utilise ''locational advantages'' and meet profit targets, but the integration of these divergent scenarios creates considerable organisational tensions. This scenario is illustrated through an analysis of the high attrition rates produced in the South Indian IT hub of Bangalore and how this is managed by one German software production company.